Rozwiąż równanie (nierówność):

a) x√2 - 3 = x - 1

b) x + (1 + x)√5 = 1

c)(x - 3)(x + 4) - 2(3x - 2) = (x - 4)²

d) 5(x - 1)² - 2(x + 3)² = 3(x + 2)² - 7(6x - 1)

e) 3(x + 1)² + (x - 4)³ = 101 + (x - 3)³

Zależy mi na dokładnym rozwiązaniu.

1

Odpowiedzi

2010-04-06T16:09:13+02:00
A) x√2-3=x-1
x√2-x=-1+3
x(√2-1)=2
x=2 ∨ √2-1=2
√2=3
sprzeczność

d)5(x-1)²-2(x+3)²=3(x+2)²-7(6x-1) 5(x²-2x+1)-2(x²+6x+9)=3(x²+4x+4)-42x+7
5x²-10x+5-2x²-12x-18=3x²+12x+12-42x+7
5x²-10x+5-2x²-12x-18-3x²-12x-12+42x-7=0
8x=32/:8
x=4

e)3(x+1)²+(x-4)³=101+(x-3)³
3(x²+2x+1)+ (x³-3x²4+3x4²-64)=101+ (x³-3x²3+3x9-27)
3x²+6x+3+x³-12x²+48x-64=101+x³-9x²+27x-27
3x²+6x+3+x³-12x²+48x-64-101-x³+9x²-27x+27=0
27x=135/:27
x=5

b)x+(1+x)√5=1
x+√5+x√5=1
x(1+√5)=1-√5
x=1-√5 ∨ 1+√5=1-√5
√5=-√5
sprzeczność

c)(x-3)(x+4)-2(3x-2)=(x-4)²
x²+4x-3x-12-6x+4=x²-8x+16
3x=24/:3
x=8


2 1 2